Sol-Gel Synthesis and Characterization of Carbon doped TiO2 based on Solanum Tuberosum Starch - Diandari Siti Nur Ichsani; Cahyorini Kusumawardani (Indonesian Journal of Chemistry and Environment, 2022)
The carbon-doped TiO2 have been synthesized through sol-gel method using Solanum tuberosum starch as carbon source.  The carbon precursor composition and reaction time were varied to study its influence to the crystal structure and electronic structure of resulted material. The C- TiO2 product was characterized by XRD, UV-Vis DRS, FTIR, and photocatalytic activity examine by methylene blue degradation. The results showed that variations in the composition of the carbon precursor and reaction time affected the characteristics of the crystal structure and photocatalyst activity of C- TiO2. The optimum variation was found in the variation of 1.5 gram carbon composition and 24 hours hydrolysis time which had the smallest particle size and lowest bandgap energy. The highest photocatalyst activity was obtained at a 24-hour reaction time variation with 59.375% percent of methylene blue degraded in the second-order reaction with a k value of 2.1351.